Increased FDG uptake on late-treatment PET in non-tumour-affected oesophagus is prognostic for pathological complete response and disease recurrence in patients undergoing neoadjuvant radiochemotherapy - Zschaeck, Sebastian; Weitz, Jürgen; Baumann, Michael (European journal of nuclear medicine and molecular imaging, 2017)
PurposeEarly side effects including oesophagitis are potential prognostic factors in patients undergoing radiochemotherapy (RCT) for locally advanced oesophageal cancer (LAEC). We assessed the prognostic value of 18F-fluorodeoxyglucose (FDG) uptake within irradiated non-tumour-affected oesophagus (NTO) during restaging positron emission tomography (PET) as a surrogate for inflammation/oesophagitis.MethodsThis retrospective evaluation included 64 patients with LAEC who had completed neoadjuvant RCT and had successful oncological resection. All patients underwent FDG PET/CT before and after RCT. In the restaging PET scan maximum and mean standardized uptake values (SUVmax, SUVmean) were determined in the tumour and NTO. Univariate Cox regression with respect to overall survival, local control, distant metastases and treatment failure was performed. Independence of clinically relevant parameters was tested in a multivariate Cox regression analysis.ResultsIncreased FDG uptake, measured in terms of SUVmean in NTO during restaging was significantly associated with complete pathological remission (p = 0.002) and did not show a high correlation with FDG response of the tumour (rho < 0.3). In the univariate analysis, increased SUVmax and SUVmean in NTO was associated with improved overall survival (p = 0.011, p = 0.004), better local control (p = 0.051, p = 0.044), a lower rate of treatment failure (p < 0.001 for both) and development of distant metastases (p = 0.012, p = 0.001). In the multivariate analysis, SUVmax and SUVmean in NTO remained a significant prognostic factor for treatment failure (p < 0.001, p = 0.004) and distant metastases (p = 0.040, p = 0.011).ConclusionsFDG uptake in irradiated normal tissues measured on restaging PET has significant prognostic value in patients undergoing neoadjuvant RCT for LAEC. This effect may potentially be of use in treatment personalization.
Gesehen am 27.08.2018